Pengelolaan Limbah Bahan Berbahaya Dan Beracun (Studi Kasus Industri Pembekuan Ikan PT. X) - Navisa Ika Irmayanti; Praditya Sigit Ardisty Sitogasa; Rizka Novembrianto; Pranandito Wisnu Prabowo (Jurnal Ekologi, Masyarakat dan Sains, 2023)
Abstract: PT. X is a company engaged in the field of Freezing Fish which in its production process produces B3 waste. The hazardous waste produced needs special management so that it does not pollute the environment. The purpose of this research is to determine the management of B3 waste technically based on the generation and type of B3 waste at PT. X. This research method uses primary data collection, secondary data and data analysis. PT. X has not been able to process B3 waste independently, so the manager cooperates with a third party to transport and process the resulting waste. The hazardous waste generated is Used Oil Filter (0.25 kg/month), Used Refrigerant (30 kg/month), Used lubricant packaging (0.25 kg/month), Used Oil (8.3 kg/month), Waste electronics (0.75 kg/month) as well as rags and B3 contaminated gloves (0.05 kg/month). PT. X requires TPS LB3 to store B3 waste before it is transported by a third party. The required dimensions of the TPS for hazardous waste are 4 m2